2004
DOI: 10.1021/jp048616o
|View full text |Cite
|
Sign up to set email alerts
|

Coil−Globule Transition of Pyrene-Labeled Polystyrene in Cyclohexane:  Determination of Polymer Chain Radii by Fluorescence

Abstract: The coil−globule transition of a polystyrene chain (M w = 113 000, M w/M n = 1.03) randomly labeled with a pyrene derivative was studied in cyclohexane under dilute conditions by fluorescence. The coil−globule transition temperature was found to be around 25 °C from the presence of a break point in the pyrene excimer-to-monomer fluorescence intensity ratio plot with temperature. Analysis of the pyrene monomer fluorescence intensity decays with the fluorescence blob model modified to consider the presence of gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
66
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(73 citation statements)
references
References 43 publications
7
66
0
Order By: Relevance
“…polystyrene [9][10][11] and poly(methyl methacrylate) [18][19][20] solutions are characterized by mild, van der Waals type monomersolvent interactions. Experimental data on polystyrene yield curves of the swelling parameter a versus s [such as Fig.…”
Section: Discussion and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…polystyrene [9][10][11] and poly(methyl methacrylate) [18][19][20] solutions are characterized by mild, van der Waals type monomersolvent interactions. Experimental data on polystyrene yield curves of the swelling parameter a versus s [such as Fig.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…2,3 Aspects of the same physics influence a variety of phenomena with applications in responsive materials, [4][5][6] hetero-polymer and protein folding, 7 native DNA packing, polymer network collapse, 8 and interpolymer complexes. Most experiments focused on the mechanism of coil-to-globule transition have been carried out using solutions of polystyrene in cyclohexane [9][10][11] or poly(N-isopropyl acrylamide), PNIPAAm, in water. [12][13][14][15][16][17] A number of investigations focused on poly(methyl methacrylate) in appropriate Y solvents [18][19][20] or on solutions of macromolecules containing polar groups or even of polyelectrolytes in water.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the incorporation of luminescent aromatic molecules in polymers as covalently attached chromophores or dispersed dyes has been extensively investigated to obtain accurate information on polymer conformations, [1][2][3][4][5][6] polymer blend compatibility, [5,7,8] polymer chain deformation and alignment. [9][10][11][12][13] The fluorescence response usually depends on the luminescence of the isolated chromophores, or on the formation of an excimer-type emission band.…”
Section: Introductionmentioning
confidence: 99%
“…This confirms that the incorporation of %2 mol-% of pyrene moieties along the chain does not significantly affect the solution properties of PNIPAM. Relevant reports by Martinho et al [19,21,81,82] and Winnik [83] also revealed that the incorporation of %1 -5 mol-% of pyrene units into PNIPAM chains does not result in discernible effects on their phase behavior.…”
Section: Resultsmentioning
confidence: 91%
“…In a very poor solvent, the dominance of attractive segment-segment over segment-solvent interactions will force the polymer chain to collapse into the globular states. [1,2] Due to its partial resemblance to protein and DNA folding, [3][4][5] the conformational transition of long polymer chains from the extended coil state to compact globules (coil-to-globule transition) has been the subject of extensive studies in the past few decades, [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] which mainly focused on the thermodynamics of the coil-to-globule transition, i.e., the evolution of equilibrium chain conformations as the solvent quality slowly varies to span across the u-solvent condition.…”
Section: Introductionmentioning
confidence: 99%